Ceramic matrix composite
Patent Information
- Application Number
- JP2026519212
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-27
- Publication Date
- 2026-10-16
Smart Images

Figure 2026534509000001_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present disclosure relates to ceramic matrix composites, in particular to a method for producing the above composites and their potential uses. In particular, the present disclosure relates to a method for producing a silicon carbide fiber-reinforced silicon carbide composite (SiC / SiC) and the application of the above composite in components for fusion reactors. BACKGROUND ART
[0002] SiC / SiC is a type of ceramic matrix composite (CMC) that has gained increasing attention in recent years as an alternative to metal alloys in applications such as gas turbines and fission cladding. SiC / SiC, and CMCs more generally, are material systems made from ceramic fibers or particles present in a ceramic matrix phase. The desirable properties of SiC / SiC composites include high thermal stability, mechanical stability, and chemical stability, and also provide a high strength-to-mass ratio.
[0003] Existing approaches for manufacturing SiC / SiC are chemical vapor infiltration (CVI), slurry impregnation and hot pressing (HP), and polymer impregnation and pyrolysis (PIP).
[0004] CVI produces high-purity SiC, but the resulting composite is highly porous (10% to 20%), which adversely affects performance, and this problem becomes more severe as the part thickness increases. It is currently not possible to produce parts thicker than 1 mm without resulting in significant internal porosity. The process is also very slow (requiring several weeks of continuous CVI for a single part), expensive, and not applicable to complex shapes such as curved surfaces, because the raw fiber preform can only be formed using weaving (flat panels) or braiding (tubular objects). Furthermore, CVI-produced SiC / SiC typically has a fiber volume fraction of 30 vol% to 40 vol%, which adversely affects strength.
[0005] While slurry impregnation and hot pressing methods yield high-density products, they limit the geometric shape due to the application of uniaxial load during hot pressing. Furthermore, they require very expensive equipment that is not particularly suitable for mass production and is not readily available at the relevant scale. The pressure applied can also damage the fibers in the composite, potentially causing cracks in the matrix and between phases. Additionally, the temperatures used during hot pressing are often higher than the temperature limits of the fibers, leading to unfavorable grain growth, deformation, and loss of tensile strength.
[0006] The PIP method involves impregnation of a precursor polymer followed by a heat treatment that converts the polymer to SiC. During this process, the polymer can undergo significant volume shrinkage (approximately 65% to 70%), requiring multiple PIP cycles (usually 8 to 10) to increase the density of the composite, thus being very time-consuming and expensive. The process also has concerns as it forms complex geometric shapes because the material starts from raw fibers and can only be formed using weaving (flat panels) or braiding (tubular structures). The PIP matrix also remains semi-amorphous even after high-temperature heat treatment designed to crystallize it, which negatively impacts the material's high-temperature properties and irradiation resistance. [Overview of the Initiative] [Problems that the invention aims to solve]
[0007] Therefore, there is a need for alternative methods of manufacturing SiC / SiC (and similar) composites that are high-density, high-purity, and can be formed into the geometric shapes and thicknesses required in the fusion industry and other sectors. [Means for solving the problem]
[0008] The present invention is defined in accordance with the independent claims. Other features will be understood from the dependent claims and the description herein. Embodiments described but not included in the scope of the claims should be construed as merely examples for a better understanding of the present invention.
[0009] Exemplary embodiments are given in view of addressing at least some of the difficulties faced in current approaches to manufacturing ceramic matrix composites such as SiC / SiC, whether those difficulties are specifically mentioned above or otherwise can be understood from the discussion herein.
[0010] One aspect of the present invention provides a method for forming a non-oxide ceramic matrix composite such as SiC / SiC. The method includes the steps of: forming a prepreg composition from fibers of a non-oxide material (e.g., silicon carbide) and a non-oxide powder (e.g., silicon carbide); compacting the prepreg composition; forming a preceramic composition by pressurizing the compacted prepreg composition with a fluid polymer and crosslinking under pressure; and heat-treating the preceramic composition to form a non-oxide ceramic matrix composite (CMC). The pressurizing, crosslinking, and heat-treating steps can be repeated (for the obtained non-oxide CMC) to improve the density of the CMC. For example, the steps may be repeated two to three times, preferably at least three to four times.
[0011] Preparing prepregs using non-oxide powders (e.g., through aqueous slurry impregnation) reduces the number of densification cycles required, while the crosslinking process under pressure improves strength and similarly reduces the number of densification cycles required. The pressure applied during the pressurized impregnation and crosslinking phases may be about 6 bar (or between 4 and 6 bar), and the temperature may be about 130°C to 250°C (particularly between 180°C and 250°C, more preferably between 200°C and 250°C), resulting in an energy-efficient manufacturing process while achieving a low number of cycles for densification.
[0012] In some examples, the process of forming a prepreg includes a step of forming a prepreg that is both releaseable and adhesive by adding a binding additive and a tackifying additive during the impregnation step, the additives may be polymers belonging to the alcohol group of organic compounds, for example, at least one of the polymers may be ethylene-based. Advantageously, the prepreg may be manufactured to facilitate molding into complex molds and laminating multiple layers of prepregs into suitable molds. For example, layers of prepreg material can be laminated to thicknesses between 1 and 6 mm, for example, greater than 3 mm, without concern according to the method of the present invention. In some examples, a de-adhesion step including heat treatment can be performed between compaction and pressure impregnation to remove the binding agent / tackifying agent (if present), and for some ceramics, pre-sintering of the composition can be performed, which also has the advantage of opening pores and flow channels for preparation for pressure impregnation.
[0013] Overall, the exemplary method improves upon existing methods for manufacturing CMCs (SiC / SiC, etc.) by its ability to produce high-purity CMCs with high overall material density in large quantities, with complex geometric shapes, all within a shortened timeframe and at low cost.
[0014] In one example, the method may include a step of coating a non-oxide ceramic matrix with a non-oxide composition such as silicon carbide, which makes the CMC particularly suitable for use in fusion reactor components by making it airtight against hydrogen. Alternatively, the coating step of an environmental barrier coating may make the composite more suitable for other applications, such as aerospace.
[0015] In specific embodiments of the present invention, a method can be provided for forming a non-oxide ceramic matrix composite (SiC / SiC, etc.) starting from a bundle of fibers, which are well known to those skilled in the art as a tow; that is, the method can be applied to so-called tow pregs.
[0016] In other words, the method may include the steps of forming a prepreg composition from a single tow of a non-oxide material (e.g., silicon carbide) and a non-oxide powder (e.g., silicon carbide); molding and compacting the prepreg composition; subsequently forming a preceramic composition by pressurizing the compacted prepreg composition with a fluid polymer and crosslinking it under pressure; and heat-treating the preceramic composition to form a non-oxide ceramic matrix composite (CMC). The pressurizing, crosslinking, and heat-treating steps can be repeated (for the obtained non-oxide CMC) to improve the density of the CMC. For example, the process may be repeated two to three times, preferably at least three to four times.
[0017] The tow can be stored or formed into the desired shape as a tow preg immediately after being combined with non-oxide powder using a suitable process such as wet winding.
[0018] Otherwise, all the processes and any features described above (and those not otherwise specified herein) apply, along with corresponding advantages, to starting from multiple fibers or prepregs as individual toes (usually formed from multiple toes woven into a fabric).
[0019] Preferably, in another embodiment of the present invention, a fusion reactor is provided comprising a non-oxide ceramic matrix composite formed by the method described above. In particular, the fusion reactor may include a vacuum vessel and a bleeder blanket for the vacuum vessel, the bleeder blanket comprising a SiC / SiC composite (or another non-oxide ceramic matrix composite) provided with a suitable SiC (or similar) coating.
[0020] As used herein, unless otherwise explicitly specified, all numerical values representing values, ranges, quantities, or percentages shall be interpreted as if preceded by the word “approximately,” even if the word is not explicitly stated. As used herein, the terms “approximately” or “substantially” mean ±5% of the stated value. Furthermore, any numerical range described herein shall be interpreted as including all subranges contained within that range, and the terms “from” and “to” for a pair of values shall be interpreted as indicating that those values fall within that range. The singular form includes the plural form, and vice versa. In addition, although the present invention is described using the term “including,” the processes, materials, and coating compositions detailed herein may also be described as “essentially consisting of” or “consisting of.”
[0021] To better understand this disclosure, please refer here to the attached drawings, which are for illustrative purposes only. [Brief explanation of the drawing]
[0022] [Figure 1]Shows an exemplary manufacturing method for ceramic matrix composites such as SiC / SiC. [Figure 2] Shows an exemplary method for storing a prepreg formed by the method according to claim 1. [Figure 3] Shows an exemplary microstructure of a SiC / SiC composite. [Figure 4] Shows an enlarged view of an exemplary matrix of a SiC / SiC composite. [Figure 5] Shows improvements resulting from repeated processing of an exemplary SiC / SiC composite. [Figure 6] Shows an exemplary nuclear fusion reactor. MODE FOR CARRYING OUT THE INVENTION
[0023] At least some of the following exemplary embodiments provide an improved method for producing ceramic matrix composites (CMC) such as silicon carbide silicon carbide (SiC / SiC). The exemplary method produces composites that are dense throughout the entire thickness of the material, can be formed into various geometric shapes, and are far more efficient at achieving the desired densification.
[0024] Figure 1 shows an exemplary method 100 for forming a non-oxide ceramic matrix composite, that is, a material reinforced with fibers formed from any suitable ceramic material that can be classified as a non-oxide such as carbide, boride, nitride, and silicide. The following description will be made primarily with reference to preferred embodiments for forming a SiC / SiC ceramic matrix composite.
[0025] Step 102 of the method includes the step of forming a prepreg composition. The prepreg composition comprises multiple fibers of a non-oxide material, preferably silicon carbide (e.g., Hi-Nicalon Type S or Tyranno SA3 or SA4). Preferably, the fibers can be recoated with an interphase coating (e.g., pyrolysis carbon or boron nitride) after heat treatment to remove any protective sizing agents. In a preferred example, the non-oxide material may be, for example, a fabric woven together from multiple toes, where each toe is woven to contain multiple unidirectional fibers in a single bundle. Preferably, the following description assumes that the prepreg composition is formed from the above-mentioned multiple fibers woven into a fabric. However, it will be readily apparent to those skilled in the art that the described method can be equally applied to starting with a prepreg composition formed from individual toes, for example, a towpreg composition obtained using a wet winding process, without requiring significant changes to the steps of the described method.
[0026] Preferably, the process of forming the prepreg composition may include impregnating fibers with a slurry. To reduce the burden on human health and the environment and to increase the time available for subsequent lamination of the prepreg, the slurry is preferably aqueous (i.e., an aqueous suspension). The slurry contains a non-oxide powder composition, such as SiC, in which the powder particles are preferably submicron in size. Preferably, these submicron powders are less toxic and less expensive to produce than the ordinary nanoscale powders used in slurry impregnation and alternative CMC methods such as the HP method. Other exemplary non-oxide compositions for the powder include zirconium diboride / zirconium carbide and hafnium diboride / hafnium carbide, with the optional addition of small amounts of tungsten and / or SiC.
[0027] The slurry may also contain at least one binding additive and at least one tackifying additive. In preferred examples, each of the binding additive and tackifying additive is polymer-based, particularly polymers belonging to the alcohol group of organic compounds (e.g., ethylene-based polymers). When impregnated with a slurry containing a binding agent and a tackifying agent, the result is a prepreg that is "adhesive" or "adheres" to it. This makes prepregs prepared in this manner particularly convenient in later stages of manufacturing, as the prepreg is flexible and easily applied to molds, for example. The adhesion of the prepreg also allows for the formation of thicker laminates by preventing individual prepreg layers from sliding during compaction, which often leads to defects, such as wrinkles.
[0028] In particular, the slurry does not contain any (other) additives typically used in CMC manufacturing methods that enhance later stages of production, such as additives required for calcination. This results in very high-purity CMC and eliminates the need for manufacturing phases based on those additives (e.g., the second phase during densification).
[0029] Figure 2 shows an example process in which the prepreg is prepared for storage (and later retrieval). Specifically, Figure 2 shows an example process that may take place between steps 102 and 104 (described later) in Figure 1.
[0030] Preferably, in step 202, the prepreg composition may be dried and placed between two plastic release films. In other words, each main surface of the prepreg composition may be encased in a peelable sealant layer. In step 204, the encased prepreg composition may be rolled up and frozen (for example, by storing it in a freezer). In step 206, the rolled prepreg may be thawed and unrolled, and then cut into a shape of appropriate size. After cutting, the release film may be peeled to expose the adhesive surface of the peelable and adhesive prepreg.
[0031] Returning to Figure 1, in step 104, the prepreg composition can be suitably molded, which can be achieved through the placement of the prepreg on a suitable mold. Due to the flexibility of the prepreg composition, the mold may be a flat sheet, may include a curved geometric shape, or may be a complex arrangement of geometric features such as a flat surface, curved, recurved, tubular, or conical shape. Preferably, multiple layers of the prepreg composition are laminated on the mold based on the desired thickness of the resulting CMC. In particular, for the use of fusion components, it is desirable to produce a CMC with a thickness between 1 mm and 6 mm, for example, about 3 mm. As an example, for SiC / SiC composites, assuming a prepreg with a 50% fiber volume fraction, about 12 layers can be applied to the mold to achieve a composite with a thickness of approximately 3 mm.
[0032] However, it should be understood that this is merely one example of prepreg molding. In another example, the prepreg can be molded directly during the prepreg formation phase. This may be suitable, for example, when the shape is a very simple geometric shape, such as a flat sheet or a cylinder. This may also be suitable when a wet winding process (or similar) is used for molding.
[0033] In step 106, the molded prepreg is compacted (i.e., compressed) in an autoclave, as is well known to those skilled in the art. In the method of the present invention, compaction can be carried out by applying a positive pressure of up to about 10 bar. Furthermore, in the method of the present invention, compaction can be carried out at a temperature of up to about 200°C. As is well known to those skilled in the art, the compaction process is designed to remove macropores from the prepreg composition, leaving only micropore channels that can be filled later in the process.
[0034] After compaction, the compacted prepreg may optionally be heat-treated to remove any remaining polymers (i.e., binders and tackifiers) from the slurry phase, as well as any impurities such as oxides, and to pre-calcine any non-oxide powders in the prepreg composition. Heat treatment also opens pores and flow channels in the compacted prepreg.
[0035] However, this process may only be desirable for certain non-oxide materials. For example, the process is undesirable for unfired ceramics, such as hafnium carbide or ceramic borides. In the production of SiC / SiC composites, the compacted prepreg can be heat-treated to approximately 1650°C to 1850°C. At this stage of production, the SiC / SiC composite may have a density of approximately 65% to 70% of the final desired density. For unfired ceramics, heat treatment at approximately 300°C to 500°C may be appropriate.
[0036] In step 108, the compacted (and optionally heat-treated) prepreg may be pressure-impregnated with a fluid polymer (e.g., polycarbosilane and its derivatives such as allylhydride polycarbosilane, or phenolic resin, or polysilazane, or a combination thereof) and crosslinked (i.e., solidified) under positive pressure (i.e., above atmospheric pressure) to form a preceramic composition. That is, pressure impregnation and crosslinking are carried out simultaneously under positive pressure. Chemicals may be mixed with the fluid polymer before pressure impregnation to accelerate and / or improve crosslinking. As will be well understood by those skilled in the art, this process gives strength to the resulting CMC by forming a network of non-oxide material (e.g., SiC) that bond the particles together, thereby increasing the density of the composition by filling the voids around the compacted powder particles with a liquid polymer. Applying pressure during crosslinking enables the achievement of high density in the resulting CMC.
[0037] In some cases, the fluid polymer may be preheated to reduce its viscosity before pressure impregnation. In some examples of the present invention, the polymer may be injected by applying positive pressure after being heated to about 60°C. The pressure is preferably about 6 bar, or at least between 4 and 6 bar.
[0038] It is understood that different pressures may be used depending on the degree of preheating, etc., but the examples of the present invention have been found to provide an efficient route for manufacturing. It will be understood by those skilled in the art that pressure impregnation may also include the step of placing the compacted prepreg in a mold or bath to receive the fluid polymer ready for impregnation.
[0039] In one example, crosslinking may involve placing the polymer-impregnated sample in a suitable oven and heating it to about 130°C to about 250°C while maintaining pressure from the pressure impregnation process (e.g., between 4 and 6 bar, preferably about 6 bar). In another example, crosslinking can be carried out at a temperature of about 180°C to about 250°C. In yet another example, crosslinking can be carried out at a temperature of about 200°C to about 250°C. The advantage of step 108 is that, because the non-oxide composite contains powder and is pre-compacted, it allows for more effective and efficient densification of the portion, and the use of pressure ensures even impregnation of the polymer, resulting in a density of over 90%.
[0040] In step 110, the preceramic resulting from pressure impregnation and crosslinking is heat-treated, i.e., thermally decomposed, to form a non-oxide CMC, such as SiC / SiC. Here, the heat-treating step may include heating the preceramic / solid polymer material to about 800°C to about 1100°C. In a preferred example, the preceramic is heated to about 1000°C. In this phase, the polymer portion of the composition is reduced by about 25% to 35% by mass and by about 50% to 70% by volume.
[0041] In some examples, steps 108 and 110 may be repeated to further increase the density of the CMC. That is, once the CMC is produced after step 110 so that it undergoes pressure impregnation with the (same) fluid polymer and crosslinking of the polymer, the resulting CMC can be used as input to step 108. The pressure-impregnated and crosslinked CMC is then used as input to step 110 for further heat treatment. At this stage, steps 108 and 110 are performed substantially twice. In some examples, steps 108 and 110 can be performed either three or four times in total, i.e., steps 108 and 100 are performed two or three times on the CMC.
[0042] Once the desired number of repetitions have been performed, the non-oxide CMC may optionally be crystallized in step 112. Preferably, the crystallization may further include heating the non-oxide CMC to a temperature higher than the temperature at which it was heated in the (repeated) step 110. For example, the non-oxide CMC may be heated to about 1200°C to about 1600°C, and preferably to about 1400°C.
[0043] At this stage, CMC can optionally be coated using a non-oxide composition. In some cases, the coating may be achieved by chemical vapor deposition. Preferably, the CMC may be coated with SiC. This is particularly advantageous for intended use in fusion reactors, for example, in bleeder blankets where the CMC may be exposed to liquid metal / molten salt and which need to be a closed space to avoid hydrogen (i.e., tritium) leakage. In other industries, it is understood that the CMC may not require coating, or the addition of a simple, environmentally friendly coating may be desirable.
[0044] Figures 3 to 5 show scanning electron microscope images of exemplary SiC / SiC produced using the method described above. Figure 3 shows the microstructure of exemplary SiC / SiC, indicating good powder impregnation (particularly between fiber bundles - small circles). Figure 4 is a magnified view of the matrix showing SiC particles surrounded by a network of polymer-derived SiC. Figure 5 shows the improvement in density of the SiC / SiC composite by repeating steps 108 and 110, and a comparison with SiC / SiC produced by the CVI approach. Unlike CVI, the method of the present invention makes it possible to produce a composite with high density throughout the entire thickness.
[0045] Unlike the HP method, the present invention is not limited to any particular geometric shape because, compared to other methods (not shown), pressure is not applied at high temperatures (>1000°C). This allows for the use of autoclaves to form and compact more complex composite structures at lower temperatures (<200°C). The pressure applied during pressurized impregnation is also applied to the impregnated polymer, not to the material itself. Crosslinking is also carried out at relatively low temperatures (e.g., 200 to 250°C), allowing for the use of more complex and lower-cost molds. Heat treatment at higher temperatures (>800°C) is carried out without pressurization in the furnace. Unlike the PIP method, the present invention pre-fills the fibers with powder (i.e., prepreg formation), which means that fewer polymer impregnation cycles are required for high density (e.g., 3 to 4 cycles, as shown in Figure 5), instead of the usual 8 to 10 cycles. Furthermore, adverse effects associated with the semi-amorphous state of the SiC matrix derived from the final polymer are minimized because the matrix composition is mostly manufactured from crystalline powder particles.
[0046] Figure 6 shows an exemplary fusion reactor 600 including a non-oxide ceramic matrix composite. The non-oxide ceramic matrix composite can be suitably formed using the method 100 described above. In particular, reactor 600 may include a SiC / SiC ceramic composite.
[0047] Here, the reactor 600 particularly includes a vacuum vessel 602, a plurality of first wall modules 604, and a plurality of bleeder blanket modules 606. In a preferred example of the reactor 600, the bleeder blanket modules may preferably include SiC / SiC.
[0048] Other exemplary uses of CMC include accident-tolerant fuels and sixth-generation fuel (GEN VI fuel) cladding and other in-core materials, thruster chamber linings and nozzles for advanced (lightweight) rocket systems, and shrouds, blades and combustion chamber liners for next-generation aircraft.
[0049] To summarize, we have described exemplary methods for manufacturing ceramic matrix composites such as SiC / SiC. The exemplary embodiments described provide a more efficient and environmentally friendly approach to manufacturing CMCs, as well as resulting in improved materials.
[0050] The CMCs described herein can be industrially produced. Industrial applications of exemplary embodiments will become apparent from the discussion in the specification.
[0051] Preferred embodiments of the present invention have been shown and described, but those skilled in the art will understand that modifications can be made without departing from the scope of the invention as defined in the claims.
[0052] In connection with this application, please note all documents and papers filed concurrently with or prior to this specification and made available to the public together with this specification. The contents of all such documents and papers are incorporated herein by reference.
[0053] All features and / or all steps of any method or process disclosed herein may be combined in any combination, except for any combination in which at least some of such features and / or steps are mutually exclusive.
[0054] Each feature disclosed herein may be replaced by an alternative feature serving the same, equivalent, or similar purpose unless otherwise expressly stated. Therefore, unless otherwise specifically stated, each disclosed feature is merely an example within a general range of equivalent or similar features.
[0055] The present invention is not limited to the details of the embodiments described herein. The present invention extends to any novel one or a novel combination thereof of the features disclosed herein, or any novel one or a novel combination thereof of the steps of the methods or processes disclosed herein. [Explanation of symbols]
[0056] 600 fusion reactors 602 Vacuum container 604 First Wall Module 606 Breeder Blanket Module
Claims
1. A method for forming a non-oxide ceramic matrix composite, A process of forming a prepreg composition from non-oxide material fibers and non-oxide powder, A step of compacting the prepreg composition, A step of forming a preceramic composition by pressurizing the compacted prepreg composition with a fluid polymer and crosslinking it under pressure, The process involves heat-treating the pre-ceramic composition to form a non-oxide ceramic matrix composite. Methods that include...
2. The method according to claim 1, wherein the fibers of the non-oxide material contain silicon carbide.
3. The method according to claim 1, wherein the step of forming the prepreg includes the step of impregnating the fibers with an aqueous slurry containing the non-oxide powder.
4. The method according to claim 1, wherein the powder of the non-oxide composition contains silicon carbide.
5. The method according to claim 3 or 4, wherein the slurry contains at least one of a binding additive and a tackifying additive.
6. The method according to claim 5, wherein the additive is a polymer belonging to the alcohol group of organic compounds.
7. The method according to claim 1, wherein the pressure impregnation includes a step of preheating the fluid polymer.
8. The method according to claim 1, wherein the pressure impregnation includes a step of applying a pressure of up to 6 bar, preferably between about 4 bar and about 6 bar.
9. The method according to claim 1, wherein the crosslinking step includes a step of heating at approximately 130°C to approximately 250°C, preferably approximately 180°C to approximately 250°C, and more preferably 200°C to approximately 250°C.
10. The method according to claim 1, wherein the heat treatment step includes a step of heating at approximately 800°C to approximately 1100°C.
11. Furthermore, the method according to claim 1, comprising, in order, the steps of pressurizing the non-oxide ceramic matrix composite with the fluid polymer, crosslinking it, and heat treating it.
12. The method according to claim 11, further comprising the step of pressurizing the fluid polymer, crosslinking it, and heat-treating it, repeated at least two times, preferably three times, and more preferably four times.
13. The method according to claim 1, further comprising a step of heat-treating the prepreg composition to about 1650°C to about 1850°C between the compaction step and the pressure impregnation step.
14. The method according to claim 1, further comprising a step of heat-treating the prepreg composition to about 300°C to about 500°C between the compaction step and the pressure impregnation step.
15. The method according to claim 1, further comprising the step of placing the prepreg composition on a mold before the compaction step.
16. The method according to claim 15, wherein the step of placing the prepreg composition on a mold includes the step of laminating a plurality of layers of the prepreg composition on the mold.
17. The method according to claim 16, wherein the step of laminating a plurality of layers of the prepreg composition onto the mold includes a step of laminating layers thicker than 3 millimeters.
18. The method according to claim 1, wherein the step of compacting the prepreg composition includes applying a pressure of up to about 10 bar to the prepreg composition.
19. The method according to claim 1, wherein the step of compacting the prepreg includes a step of heating the prepreg to a maximum of approximately 200°C.
20. The method according to claim 1, further comprising the step of coating with a non-oxide ceramic matrix.
21. The method according to claim 20, wherein the coating comprises a non-oxide composition.
22. The method according to claim 21, wherein the coating containing the non-oxide composition contains silicon carbide.
23. A fusion reactor comprising a non-oxide ceramic matrix composite formed by the method described in claim 1.
24. A fusion reactor according to claim 23, comprising a vacuum vessel and a bleeder blanket for the vacuum vessel, wherein the bleeder blanket comprises a non-oxide ceramic matrix composite formed according to claim 22.